UJI KELAYAKAN APRON DENGAN MENGGUNAKAN IMAGING PLATE (IP) DI INSTALASI RADIOLOGI RUMAH SAKIT YASMIN BANYUWANGI - Sri Sugiarti (Health Care Media, 2021)
Test the Feasibility of the Apron Using an Imaging Plate (IP) at the Radiology Installation Yasmin Banyuwangi Hospital. Apron leak test at the Radiology Installation Yasmin Banyuwangi Hospital using an imaging plate on X-ray aircraft without fluoroscopy. The purpose of this study is to determine the number of aprons that are suitable for use in the Radiology Installation of Yasmin Banyuwangi Hospital. The research was carried out by physical apron testing, then irradiate the surface of the apron using X-ray aircraft without fluoroscopy equipped by dividing 4 parts on a cassette imaging plate. The results of radiographs from three aprons after being interpreted by 3 respondents indicated that been tested in a Radiology Installation of Yasmin Banyuwangi Hospital only number three apron was feasible, although the physical condition of the apron is not good and there is no fracture on the results of the radiograph. While the number one and two aprons are not feasible to use because the physical condition of the apron is not good and some exceed the eligibility criteria used in the radiograph.